Development of the Library Material Collection of the National Institute of Technology Library in Collaboration with Chiness Corner Amanda Nurul - Amalia, Amanda Nurul; Rachmawati, Tine Silvana (Universitas Negeri Padang, 2024)
Collaboration within the library is important where it provides benefits and promotes development. Here we discuss further the development of the ITENAS library material collection in the Chiness Corner Collaboration, using the research method, namely the descriptive qualitative method with an observational approach to directly observe the collection development process and interactions between library managers and users. This research shows that collaboration with Chinese Corner makes a significant contribution to the development of library material collections at the ITENAS Library. Library management actively coordinates with Chinese Corner staff to understand user needs regarding library materials. The process of selecting and acquiring library materials is carried out by considering user preferences and relevance to the Chinese Corner program. The observation results also reveal the importance of effective processing of library materials. The indexing and classification process is carried out carefully to ensure accessibility and easy search. Collaboration with Chinese Corner makes it possible to provide special space or shelves to display library materials related to China, making it easier for users to find and utilize these collections.Keywords: library, collection development, collaboration